ANALISIS PENGARUH KUALITAS PELAYANAN PENYULUH PERTANIAN TERHADAP KEPUASAN PETANI DALAM PENGEMBANGAN USAHA TANI DI KABUPATEN PIDIE - Mujiburrahmad, Mujiburrahmad; Baihaqi, Akhmad; Manyamsari, Ira (Jurnal AGRISEP, 2020)
Agricultural activities still have a very strategic role in supporting national development, both for economic growth and equitable development. The strategic role of the agricultural sector for economic growth includes: food producers for the population of Indonesia, foreign exchange earners through exports, providers of industrial raw materials, increased employment and business opportunities, increased GDP, poverty alleviation and improvement of agricultural human resources through agricultural extension activities. The purpose of this study is to, (1) Knowing farmers' satisfaction with extension services in farming development in Pidie District, and (2) Knowing the relationship between the quality of agricultural extension services to the development of farming in Pidie District. This research was carried out in the Dayah Syarief Village, Mutiara District, Pidie District. The sample in this study were all farmers who numbered 90 people. The independent variables in this study are: (X1), Response (X2), Confidence (X3), Empathy (X4), Physical Evidence (X5) and Farmer Decision (Y) as the dependent variable. Data is collected using the survey method through a questionnaire filled out by Farmers. The data processing in this study will use the SPSS program (Statistical Package for the Social Science). The satisfaction of farmer with extension services in farming development in Busu Dayah Syarief Village, Mutiara District, Pidie District based on the results of research on Farmer Satisfaction variables obtained an average value of (4.18), so that respondents' assessment of the Farmer Satisfaction variable was influenced by variables of reliability, responsiveness , Belief, empathy and physical evidence. The relationship of the quality of agricultural extension services to the development of farming in Busu Dayah Syarief Village, Mutiara District, Pidie District, based on the results of the analysis concluded that of the five variables studied, it turns out the Confidence variable (X3) has the most dominant influence of 0.422% on Farmer Satisfaction. The relationship between the dependent and independent variables is each variable Reliability (X1), Responsiveness (X2), Confidence (X3), Empathy (X4), and Physical Evidence (X5) to Farmer Satisfaction with a correlation index of 0.978 or 97.8 % This means that the relationship is very strong. Then the index of determination of each variable Reliability (X1), Responsiveness (X2), Confidence (X3), Empathy (X4), and Physical Evidence (X5) is 0.957 or 95.7%, this means that the 5 variables have a significant effect towards farmer satisfaction in farming development, and by 4.3% which is influenced by other variables not examined in this study.